Associations between Developing Sexuality and Mental Health in Heterosexual Adolescents: Evidence from Lower- and Middle-Income Countries-A Scoping Review - Neelam Saleem Punjani; Elizabeth Papathanassoglou; Kathleen Hegadoren; Saima Hirani; Zubia Mumtaz; Margot Jackson (MDPI AG, 2022)
Background: During puberty and emerging sexuality, adolescents experience important physical, mental, and social transformations. In the process of dealing with these changes, adolescents can become potentially vulnerable to mental health problems. Aim: The aim is to identify and synthesize published research evidence on sexuality-related mental health stressors among adolescent girls and boys, identify gaps (if any) in the current knowledge, and contribute to the knowledge about the experiences of emerging sexuality and health among adolescents, to further inform research, practice, and policy initiatives in sexual health. Design: A scoping literature review of peer-reviewed articles published between 1990 and 2021. MEDLINE, CINAHL, EMBASE, PsycINFO, Global health, ERIC, and Sociological Abstracts databases were searched for research studies that reported experiences of sexuality-related mental health issues and symptomatology of adolescents. We targeted studies conducted with adolescent populations between ages 10-19 years living in LMICs. Results: Data from 12 published research papers, including 8 qualitative studies, 3 quantitative studies, and 1 mixed method study, were systematically analyzed. Four major themes and four sub-themes were identified regarding the sexual and mental health of adolescents: (1) Relationship of sexuality and mental health; (2) Social and cultural influences; (3) Challenges in seeking sexuality information and services among adolescents; and (4) Educational needs among adolescents related to sexuality. Conclusions: Lack of social support, unmet needs for accessible adolescent-friendly sexual health services, counseling, and age-appropriate information may be associated with several mental health stressors and symptoms, such as sadness, depressive and anxiety symptomatology, regret, fear, embarrassment, low self-esteem, guilt, shame, and anger. Therefore, tackling sexuality-related stressors could play an important role in addressing the overall well-being of young people. Future studies need to generate a deeper understanding of the concept of sexual health and its relation to mental health in diverse contexts. Implications for Practice: Health care professionals need to be aware of sexuality-related experiences of adolescent girls and boys by offering effective youth-friendly sexual and reproductive health education to support overall mental health and improve the experiences of emerging sexuality in adolescents.